(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
O artigo discute o papel do dramaturgo e analisa diversos aspectos relativos à dramaturgia no Teatro de Bonecos e no Teatro de Objetos, tais como: a importância da ação e a economia de palavras; a escolha de materiais e objetos que colaboram na definição da dramaturgia; a metáfora como recurso; a indissociação entre construção do texto e encenação. Por fim, o estudo apresenta a síntese da última aula ministrada pelo autor na sua condição de professor de Dramaturgia na Escuela de Titiriteros del Teatro General San Martín, em Buenos Aires, no ano de 2001. Palavras-chave: Dramaturgia; teatro de títeres; teatro de objetos. Abstract: This article discusses the role of the playwright and analyses various factors related to dramaturgy in Puppet Theatre and the Theatre of Objects such as: the importance of action and the economy of words; the choice of materials and objects that collaborate in the definition of the dramaturgy; the metaphor as resource; and the inseparability between construction of text and staging. Finally, the study presents a synthesis of the final class given by the author as theatre professor at the Escuela de Titiriteros del Teatro General San Martín, in Buenos Aires, in 2001. Key-words: Dramaturgy; puppet theatre; theatre of objects.